The impact of human resources practices on the degree of job satisfaction : Case study on Egyptair company - Maha Mohamed Ibrahim Basmy; Mostafa Mostafa Kamel (Cairo : Maha Mohamed Ibrahim Basmy, 2015)
The study of job satisfaction has established its importance as one of the most extensively researched topics. As a work {u2013}related attitude, it has a potential antecedents leading to it and consequences resulting from it. Organizations exploring the importance of job satisfaction, the right to use it as a tool for an added value and as a competitive advantage for these organizations. This study uses Egypt Air in the transportation sector being a case because of the importance of this sector, and also Egypt air has been considered the only Egyptian aircraft company founded in May 1932 as a state-owned company with special permitting the management to operate as if it is privately owned Egypt air is considered one of the most companies {u2013} by its nature {u2013} to face a highly competitive transportation market severely challenged by globalization, its more than others will be benefited from advantages of job satisfaction. Therefore, this study is an attempt to measure the job satisfaction of employees regarding (compensation, training, performance appraisal and hiring) practices in the studied companies. Data were collected from 450 employees from the subsidiaries of Egypt Air Company. Pearson correlation coefficient, Independent - samples 2T-Test3 & One-way Analysis of Variance 2ANOVA3 are used to test hypotheses
Thesis (M.Sc.) - Cairo University - Faculty of Commerce- Department of Business Administration
Issued also as CD
Keywords: Egyptair company; Human resources practices; Job satisfaction